The Micro-RNA Cargo of Extracellular Vesicles Released by Human Adipose Tissue-Derived Mesenchymal Stem Cells Is Modified by Obesity - Eirin, Alfonso; Meng, Yu; Zhu, Xiang-Yang; Li, Yongxin; Saadiq, Ishran M.; Jordan, Kyra L.; Tang, Hui; Lerman, Amir; van Wijnen, Andre J.; Lerman, Lilach O. (Frontiers in Cell and Developmental Biology, 2021)
Obesity is a chronic disease that interferes with normal repair processes, including mesenchymal stem/stromal cells (MSCs) function. MSCs produce extracellular vesicles (EVs) that activate a repair program in recipient cells partly via their micro-RNA (miRNA) cargo. We hypothesized that obesity alters the miRNA expression profile of human MSC-derived EVs, limiting their capacity to repair injured cells. Human MSCs were harvested from obese and age- and gender-matched non-obese (lean) subjects during bariatric or cosmetic surgeries, respectively (n=5 each), and their EVs isolated. Following high-throughput sequencing analysis, differentially expressed miRNAs were identified and their gene targets classified based on cellular component, molecular function, and biological process. The capacity of human lean- and obese-EVs to modulate inflammation, apoptosis, as well as mitogen-activated protein kinase (MAPK) and Wnt signaling in injured human proximal tubular epithelial (HK2) cells was evaluated in vitro. Differential expression analysis revealed 8 miRNAs upregulated (fold change>1.4, p<0.05) and 75 downregulated (fold change<0.7, p<0.05) in obese-EVs versus lean-EVs. miRNAs upregulated in obese-EVs participate in regulation of NFk-B and MAPK signaling, cytoskeleton organization, and apoptosis, whereas those downregulated in obese-EVs are implicated in cell cycle, angiogenesis, and Wnt and MAPK signaling. Treatment of injured HK2 cells with obese-EVs failed to decrease inflammation, and they decreased apoptosis and MAPK signaling significantly less effectively than their lean counterparts. Obesity alters the miRNA cargo of human MSC-derived EVs, as well as their ability to modulate important injury pathways in recipient cells. These observations may guide development of novel strategies to improve healing and repair in obese individuals.